Overview and analysis of occupational noise-induced hearing loss legislation in East Africa - ONYANGO, DANIEL; Kinyua, Robert; Mayaka, Abel; Kanali, Christopher (European Journal of Applied Sciences, 2021)
Hearing loss is a major occupational injury that leads to workplace accidents, miscommunication, and loss of livelihood. Conventions and Recommendations provide frameworks for mitigation of this problem. This paper evaluates legislations related to noise control in East Africa, documented and implemented by the respective governments. The scope of noise control measures and exposure limits are qualitatively examined. Results show that the details of acceptable limits are covered in both environmental and Occupational Safety and Health laws. Lower action limit of exposure to continuous noise of 85 dB(A) is specified in all the countries, but the upper action limit of 90 dB(A) is only specified by Kenya, which also specifies that hearing protection must be worn when this limit is exceeded. Impulsive noise is capped at 140 dB(A) in all the countries. Only two of the seven noise types are considered in existing laws as contributing to occupational noise-induced hearing loss.